Variasi Konsentrasi Ekstrak Annona muricata L. Terhadap Kematian Kecoak Dewasa - Agri Thael Pratama; Bambang Yulianto; Kahar Kahar (Lontara Journal of Health Science and Technology, 2024)
Vector control is an action taken to reduce the population of vectors and prevent diseases. The measurement of the cockroach population index is 3, which was found to not meet the requirements of Minister of Health Regulation No. 70 of 2016 in the raw area of the manufacturing industry. Control efforts using natural insecticides have been proven to be safe in controlling adult cockroaches. This study aims to determine the variation in concentrations of soursop leaf extract (Annona muricata L.) on the mortality of adult Periplaneta americana cockroaches in the Manufacturing Industry. The research is quasi-experimental with a posttest-only control group design involving three variations of soursop leaf extract concentrations: 5%, 6%, and 7%. Repetition was conducted six times for each concentration variation, with the population consisting of all cockroaches in the raw material area, totaling 240 cockroach samples taken using a purposive sampling technique. The data collection tools were cockroach traps and a thermo hygrometer, with data collection techniques involving measuring cockroach density, temperature, and air humidity. Soursop leaf extract at a concentration of 5% was able to kill cockroaches by 51.6%, 6% concentration by 62.3%, and 7% concentration by 81.6%. Statistical analysis using univariate and bivariate tests with one-way ANOVA showed a significant influence of the variation in soursop leaf extract concentrations, with a probability value of 0.000 (<0.05). The application of soursop leaf extract at the highest concentration of 7% can kill cockroaches by 81.6%.